Morphological alterations in salivary glands of Rhipicephalus sanguineus ticks (Acari: Ixodidae) exposed to neem seed oil with known azadirachtin concentration. (April 2016) - Remedio, R.N.; Nunes, P.H.; Anholeto, L.A.; Oliveira, P.R.; Sá, I.C.G.; Camargo-Mathias, M.I.
Highlights: Neem oil demonstrated a clear dose-dependent effect on salivary glands. Acini demonstrated cells with irregular shape, vacuolation and altered organelles. These alterations may indicate physiological impairment in salivary glands. Morphology was a helpful tool for the detection of toxic alterations. Abstract: Neem ( Azadirachta indica ) has attracted the attention of researchers worldwide due to its repellent properties and recognized effects on the morphology and physiology of arthropods, including ticks. Therefore, this study aimed to demonstrate the effects of neem seed oil enriched with azadirachtin on salivary glands of Rhipicephalus sanguineus ticks, targets of great veterinary interest because of their ability to transmit pathogens to dogs. For this, R. sanguineus semi-engorged females were subjected to treatment with neem seed oil, with known azadirachtin concentrations (200, 400 and 600 ppm). After dissection, salivary glands were collected and evaluated through morphological techniques in light microscopy, confocal scanning laser microscopy and transmission electron microscopy, so that the possible relation between neem action and further impairment in these ectoparasites feed performance could be established. Neem oil demonstrated a clear dose-dependent effect in the analyzed samples. The agranular (type I) and granular acini (types II and III) showed, particularly in individuals treated with the highest concentrations of the product, cells with irregular shape, intense cytoplasmic disorganization and vacuolation, dilation of rough endoplasmic reticulum lumen, besides alterations in mitochondrial intermembrane space. These morphological damages may indicate modifications in salivary glands physiology, demonstrating the harmful effects of compounds present in neem oil on ticks. These results reinforce the potential of neem as an alternative method for controlling R. sanguineus ticks, instead of synthetic acaricides.